AB0013 The uncoupling TJ cluster is a protective factor against osteoarthritis in Spain and UK. (23rd January 2014) - Soto-Hermida, A.; Fernandez-Moreno, M.; Oreiro, N.; Fernandez-Lopez, C.; Rego-Perez, I.; Blanco, F.J.
Abstract : Background: Oxidative stress and reactive oxygen species (ROS) production are key factors in the development of OA. Some reports have shown that those mtDNA haplogroups related with the mild uncoupling of the mitochondrial oxidative phosphorylation system (OXPHOS) are less prone to produce ROS. Objectives: Taking into account that the mtDNA haplogroup J is a protective factor against OA in Spanish populations, the aim of this work is to compare the frequency distribution of the mtDNA haplogroups in OA patients and healthy controls between United Kingdom (UK) and Spain. Methods: We used the single base extension (SBE) assay combined with polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) to obtain the European mtDNA haplogroups in 1471 OA patients and 406 healthy controls from Spain, and 453 OA patients and 280 healthy controls from UK. Some of the differential single nucleotide polymorphisms (SNPs) haplogroup J-related between both populations were also analyzed using the SBE assay. The resulting frequencies were analyzed with SPSS software (v.18) following appropriate statistical analyses. Results: The mtDNA haplogroup J appeared significantly underrepresented in OA patients from the north of Spain when compared with healthy controls (OR=0.614; 95% CI: 0.426–0.884; p=0.008). Individuals from UK carrying the mtDNA haplogroup T showed a significantly decreased risk of OA (OR=0.581; 95% CI: 0.365–0.926; p=0.021). The mtDNA haplogroup J bordered the statistical significance towards a decreased presence in healthy controls from UK (OR=1.686; 95% CI: 0.929–3.061; p=0.083). The analysis of the differentially expressed haplogroup J-related SNPs in Spain and UK, m.14798t>c, m.15257g>a and m.3394t>c, showed that the SNP m.3394t>c appeared significantly underrepresented in the UK cohort (p=0.029). Conclusions: The mitochondrial uncoupling mechanism, derived from the mtDNA haplogroups, is a protective factor against OA in Spain and UK populations. This association is probably due to a reduced reactive oxygen species production as a consequence of the climate adaptation of these mtDNA haplogroups. Disclosure of Interest: None Declared